2021
DOI: 10.3390/ijms22073519
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Mesenchymal Stromal Cells and Their Homing Capabilities to Regenerate the Intervertebral Disc

Abstract: Chronic low back pain (LBP) remains a challenging condition to treat, and especially to cure. If conservative treatment approaches fail, the current “gold standard” for intervertebral disc degeneration (IDD)-provoked back pain is spinal fusion. However, due to its invasive and destructive nature, the focus of orthopedic research related to the intervertebral disc (IVD) has shifted more towards cell-based therapeutic approaches. They aim to reduce or even reverse the degenerative cascade by mimicking the human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 109 publications
1
42
0
Order By: Relevance
“…For example, Gianluca et al [ 89 ] reported that transplanted cells could form osteophyte and might migrate out of the IVD. The uncontrollable proliferation of transplanted cells also hampered the clinical utility of cell-based therapy because of tumorigenic potential [ 89 , 101 ]. What is more, the cell-based therapy for IVDD requires a large number of injected cells (usually ~10 [7]) [ 20 ].…”
Section: Ivd Progenitor Cells In Disc Regenerationmentioning
confidence: 99%
“…For example, Gianluca et al [ 89 ] reported that transplanted cells could form osteophyte and might migrate out of the IVD. The uncontrollable proliferation of transplanted cells also hampered the clinical utility of cell-based therapy because of tumorigenic potential [ 89 , 101 ]. What is more, the cell-based therapy for IVDD requires a large number of injected cells (usually ~10 [7]) [ 20 ].…”
Section: Ivd Progenitor Cells In Disc Regenerationmentioning
confidence: 99%
“…Recently. Such iPSC have been investigated for the potential treatment of heart diseases (discussed in [85]), neurodegenerative conditions (discussed in [86][87][88][89]), and musculoskeletal conditions such as intervertebral disc repair (reviewed in [90]).…”
Section: Do Msc and Ipsc Use Different Or Similar Molecular Recognition Systems?mentioning
confidence: 99%
“…Progenitor and/or stem cell transplantation has been a long-debated treatment strategy to regenerate intervertebral disc tissues. Croft AS et al [6] conducted a narrative literature review about the effectiveness of mesenchymal stromal cell (MSC)-based therapies for degenerative disc disease. Preclinical in vitro, ex vivo, and in vivo studies presented the development of MSCs with a disc cell-like phenotype and of hydrogels and scaffolds with embedded MSCs.…”
Section: Degenerative Disc Diseasementioning
confidence: 99%